Study of Biometric Identification Method Based on Naked Footprint - Raji Rafiu King; Wang Xiaopeng (Chemical Engineering Diponegoro University, 2013)
The scale of deployment of biometric identity-verification systems has recently seen an enormous increase owing to the need for more secure and reliable way of identifying people. Footprint identification which can be defined as the measurement of footprint features for recognizing the identity of a user has surfaced recently. This study is based on a biometric personal identification method using static footprint features viz. friction ridge / texture and foot shape / silhouette. To begin with, naked footprints of users are captured; images then undergo pre processing followed by the extraction of two features; shape using Gradient Vector Flow （GVF） snake model and minutiae extraction respectively. Matching is then effected based on these two features followed by a fusion of these two results for either a reject or accept decision. Our shape matching feature is based on cosine similarity while the texture one is based on miniature score matching. The results from our research establish that the naked footprint is a credible biometric feature as two barefoot impressions of an individual match perfectly while that of two different persons shows a great deal of dissimilarity. Doi: 10.12777/ijse.5.2.29-35 How to cite this article: King, R.R. and Xiaopeng, W. (2013). Study of Biometric Identification Method Based on Naked Footprint . International Journal of Science and Engineering, 5(2),18-24. Doi: 10.12777/ijse.5.2.29-35]